Job Search With Legal and Illegal Workers: A Comparative Static Analysis - Ogbeifun, Lawrence (Economics and Business, 2020)
This paper incorporates government immigration policy variables in a job search and match framework to examine its implication on labour market outcomes. The main assumption is that illegal workers can be penalized by receiving lower equilibrium wages or face possible deportation; and government can regulate illegal workers by introducing a “caught variable”, η, in the model. By a comparative statics analysis, the study has revealed that changes in the wages of illegal workers have both direct and indirect effect on wages of legal workers. Also, an important finding is that η has positive impact on most of the labour market parameters considered in the study.